General Considerations Concerning the Principle of Territoriality of the Romanian Criminal Law - Vasile Draghici (Ovidius University Annals: Economic Sciences Series, 2016)
The expression used by the legislator in article 8 paragraph 1 of the Romanian Penal Codeshows that the Romanian criminal law enforcement is exclusive and unconditional, so regardless ofthe category of acts which are committed on the Romanian territory, the criminal jurisdiction willbe always exercised by the Romanian State through its competent bodies. From this point of view it appears that the Romanian legislator remained constant regardingthe territoriality of Romanian criminal law. In the current regulation of art. 8, paragraph 3 of the Penal Code, the offense committed inRomania, is any offense committed on the territory defined in art. 8 paragraph 2 of the Penal codeor a ship under the Romanian flag or an aircraft registered in Romania.